Solo Raya Young Muslims Generation Decision to Invest in Sharia Stocks and Green Investment - Nurohman, Yulfan Arif; Qurniawati, Rina Sari; Suparwi (SHAHIH: Journal of Islamicate Multidisciplinary, 2024)
The younger generation, particularly Muslims, faces concerns about an uncertain future, particularly regarding job opportunities. The unemployment rate in Indonesia has shown an increase, predominantly among the younger generation. This study aims to examine the impact of financial literacy, perceived risk, and high self-confidence on the decision to invest in stocks, particularly Islamic stocks. The research was conducted in the Solo Raya area with 125 Muslim youth investors as respondents, consisting of millennials and Generation Z. The analysis technique used was multiple regression, conducted using SPSS software version 24. The regression results, with a significance value below 0.05, indicate a significant influence of financial literacy, perceived risk, and high self-confidence on the investment decisions of young Muslim investors. Good financial knowledge encourages the younger generation to invest in stocks with confidence, anticipating substantial profits in the future. Perception of risk remains a consideration, leading young investors to delay investment decisions until they feel highly confident.